‘Integrated Laboratory of Scientific-academic Literacies - LILA’: facing challenges in language education - Cristovão, Vera Lúcia Lopes; Vignoli, Jacqueline Sanches; Ferrarini-Bigareli, Marlene Aparecida; Retorta, Miriam Sester (Letras, 2022)
This paper aims at presenting the results of a study whose objectives are a) to identify activities related to academic literacies carried out in Brazilian university writing laboratories; b) to present LILA as a collaborative network lab. This research was carried out within a qualitative paradigm, including a bibliographic review, document analysis of labs investigated and the description of future actions to be developed by LILA. The results indicate that these laboratories contribute to the insertion of students and researchers in academic literacies practices, and thus LILA was conceived in order to promote both scientific and academic literacies.